Assessment of eating behaviours in adult residents of Greece and Poland - an original research - Elżbieta Szczepańska; Joanna Rzepecka; Aleksandra Góra; Karolina Janion; Katarzyna Urbańczyk (National Institute of Public Health - National Institute of Hygiene, 2020)
Background: The length and the quality of life are determined by, among other things, environmental factors. The place of residence is associated with certain differences in nutritional culture, with food traditions and customs being of great importance. Also, the location of a given country in a specific climate zone has an impact on the choice of food products and their preparation. Objective: The aim of the study was to analyse eating behaviours among adult residents of Greece and Poland as well as to investigate to what extent these behaviours are impacted by the place of residence of respondents. Materials and methods: A total of 633 randomized respondents at the age of 50 or older (312 Greeks and 321 Poles) were included in the study. The author's questionnaire was used in the research. Results: A total of 41.07% of respondents, including 31.09% of Greeks and 50.78% of Poles, declared having 4-5 meals per day. Fish was consumed 1-2 times a week by 29.27% of respondents, including 23.40% of Greeks and 15.26% of Poles. Whole wheat bread was consumed several times daily by 20.7% of respondents, including 19.55% of Greeks and 21.81% of Poles. Coarse groats and pasta were consumed a few times weekly by 23.06% of respondents, including 25.64% of Greeks and 20.56% of Poles. Conclusions: Eating behaviours in adult Poles and Greeks are varied, with healthier eating habits in the latter group. There are significant differences between the intake of food products rich in fibre and omega-3 fatty acids by residents of Greece and Poland.